2010
DOI: 10.1056/nejmoa1008433
|View full text |Cite
|
Sign up to set email alerts
|

ARID1AMutations in Endometriosis-Associated Ovarian Carcinomas

Abstract: BACKGROUND-Ovarian clear-cell and endometrioid carcinomas may arise from endometriosis, but the molecular events involved in this transformation have not been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

59
1,246
7
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,500 publications
(1,361 citation statements)
references
References 32 publications
(35 reference statements)
59
1,246
7
10
Order By: Relevance
“…We identified a nonsense mutation in PRUNE2 that was reported to be a potentially oncogenic30 but not therapeutically targetable mutated genes at that time. No somatic mutation of cancer‐associated genes frequently mutated in epithelial ovarian cancer—such as TP53, 31 KRAS, 32 PIK3CA ,33 and ARID1A 34—was detected.…”
Section: Discussionmentioning
confidence: 98%
“…We identified a nonsense mutation in PRUNE2 that was reported to be a potentially oncogenic30 but not therapeutically targetable mutated genes at that time. No somatic mutation of cancer‐associated genes frequently mutated in epithelial ovarian cancer—such as TP53, 31 KRAS, 32 PIK3CA ,33 and ARID1A 34—was detected.…”
Section: Discussionmentioning
confidence: 98%
“…Using immunohistochemistry it was demonstrated that ARID1A mutations result in the loss of the protein BRG-associated factor 250a (BAF250a), which is a large subunit of transcriptionregulating Human SWI/SNF complexes and has an important role in the control of cell proliferation and tumor suppression. 7,9,10 Recently, Guan et al 11 found somatic ARID1A mutations in 10/25 uterine endometrioid carcinomas, and could also confirm a strong correlation to loss of BAF250a expression by immunohistochemistry.…”
mentioning
confidence: 88%
“…Using whole-exome sequencing, recurrent mutations in ARID1A were recently reported in ovarian clear cell carcinomas and endometrioid ovarian carcinomas by two independent groups. 7,8 Wiegand et al 7 found mutations in ARID1A in 46% of 119 ovarian clear cell carcinomas and 30% of 33 endometrioid ovarian carcinomas but in none of 76 high-grade serous carcinomas. Likewise, Jones et al 8 observed ARID1A-mutations in 57% of 42 ovarian clear cell carcinomas.…”
mentioning
confidence: 99%
See 2 more Smart Citations